Periodontal Disease and Coronary Heart Disease Incidence: A Systematic Review and Meta-analysis - Humphrey, Linda L. (Springer-Verlag, 2008)
BACKGROUND: Periodontal disease is common among adults in the US and is a potential source of chronic inflammation. Recent data have suggested an important role for chronic inflammation in the development of coronary heart disease (CHD). OBJECTIVE: To aid the United States Preventive Services Task Force (USPSTF) in evaluating whether periodontal disease is an independent novel risk factor for incident CHD. METHODS: Studies were identified by searching Medline (1966 through March 2008) and reviewing prior systematic reviews, reference lists, and consulting experts. Prospective cohort studies that assessed periodontal disease, Framingham risk factors, and coronary heart disease incidence in the general adult population without known CHD were reviewed and quality rated using criteria developed by the USPSTF. Meta-analysis of good and fair quality studies was conducted to determine summary estimates of the risk of CHD events associated with various categories of periodontal disease. RESULTS: We identified seven articles of good or fair quality from seven cohorts. Several studies found periodontal disease to be independently associated with increased risk of CHD. Summary relative risk estimates for different categories of periodontal disease (including periodontitis, tooth loss, gingivitis, and bone loss) ranged from 1.24 (95% CI 1.01–1.51) to 1.34 (95% CI 1.10–1.63). Risk estimates were similar in subgroup analyses by gender, outcome, study quality, and method of periodontal disease assessment. CONCLUSION: Periodontal disease is a risk factor or marker for CHD that is independent of traditional CHD risk factors, including socioeconomic status. Further research in this important area of public health is warranted.